2020
DOI: 10.1038/s41467-020-18933-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 vertical transmission during pregnancy

Abstract: The impact of SARS-CoV-2 infection during gestation remains unclear. Here, we analyse the viral genome on maternal and newborns nasopharyngeal swabs, vaginal swabs, maternal and umbilical cord plasma, placenta and umbilical cord biopsies, amniotic fluids and milk from 31 mothers with SARS-CoV-2 infection. In addition, we also test specific anti-SARS-CoV-2 antibodies and expression of genes involved in inflammatory responses in placentas, and in maternal and umbilical cord plasma. We detect SARS-CoV-2 genome in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
378
4
32

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(433 citation statements)
references
References 56 publications
19
378
4
32
Order By: Relevance
“…As per that classification system a neonatal congenital SARS-CoV-2 infection is confirmed if it fulfills criteria: 1) the virus is detected from amniotic fluid through intact amniotic membrane, 2) the virus is detected in the blood of newborn early after birth. In the current review, one case report [21] and one prospective study [22] confirm the intrauterine transmission by fulfilling the above mentioned case definitions. In addition, magnetic resonance imaging of the newborn [21] showed bilateral gliosis of the deep white periventricular and subcortical matter.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…As per that classification system a neonatal congenital SARS-CoV-2 infection is confirmed if it fulfills criteria: 1) the virus is detected from amniotic fluid through intact amniotic membrane, 2) the virus is detected in the blood of newborn early after birth. In the current review, one case report [21] and one prospective study [22] confirm the intrauterine transmission by fulfilling the above mentioned case definitions. In addition, magnetic resonance imaging of the newborn [21] showed bilateral gliosis of the deep white periventricular and subcortical matter.…”
Section: Discussionsupporting
confidence: 62%
“…Of 16 studies included in the current review, four [8][9][10][11] reported no vertical transmission. Twelve studies [12][13][14][15][16][17][18][19][20][21][22][23] reported vertical transmission (probable or confirmed). In 10 studies, SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) of newborns was positive and in other two studies SARS-CoV-2 IgM antibodies were detected in the newborns (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies in pregnant women with an active or a COVID-19 infection during pregnancy are warranted to investigate if morphological and histopathological placental characteristics are specific for SARS-CoV-2 infection and if these findings are associated with clinical perinatal outcome. Until now, only a few confirmed cases of vertical transmission of SARS-CoV-2 have been reported [ 4–8 ]. In our case, despite the massive placental infection, all neonatal samples were negative for SARS-CoV-2, and we found no evidence for vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In general, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy is not considered to be an increased risk for severe maternal outcomes but has been associated with an increased risk for fetal distress [ 1 ]. Localization of SARS-CoV-2 particles in placental tissue has been visualized [ 2 , 3 ], and recently, a few cases of vertical transmission of SARS-CoV-2 have been reported [ 4–8 ]. Besides related to direct in utero infection with SARS-CoV-2, the mechanisms leading to the adverse perinatal outcomes are not well understood.…”
mentioning
confidence: 99%